ANALISIS PENGENDALIAN KUALITAS PADA STASIUN PENYELESAIAN GULA MENGGUNAKAN METODE SIX SIGMA (Studi Kasus di PG Kebon Agung Malang) - Yosephine Fanisa Dhani; Mas’ud Effendi; Miftakhurrizal Kurniawan (Jurnal Ilmiah Dinamika Teknik, 2020)
Abstract PG Kebon Agung is one of the companies in the processing of cane into sugar. The main product produced by PG Kebon Agung is white crystal sugar. The process of production in Kebon Agung consist six process stations, those are milling station, purification station, evaporation station, cooking station, rounding station, and finishing station. This research focuses on finishing station. The defects that often occurs are torn packaging, dirty sugar and broken seams. This research aim to determine the causative factors that bring up the product defect, determine the ability of processes in finishing station, and determine the improvement suggestions to reduce the defective products. Data were analyzed using six sigma methods through define, measure, analyze, and improve phase. The results showed that the biggest defect type is torned packaging at 61,64% The Finishing Station at PG Kebon Agung is at the sigma level of 4.00 with DPMO of 6,159. Factors that cause defective products are human, method, material, machine, and environment. The priority for improvement is planning a frequent maintenance, implement SOP at finishing station, And provide training for workers.